1998
DOI: 10.1046/j.1365-2591.1998.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of retreatment of Thermafil and lateral condensation endodontic fillings

Abstract: The aim of the present study was to evaluate the possibility of retreating teeth obturated with: (i) Thermafil with plastic carrier, (ii) Thermafil with metallic carrier and (iii) laterally condensed gutta-percha. The following aspects were analysed: removal of obturation, time required for removal, remaining filling material and apical extrusion during reinstrumentation. Thirty human teeth with a single canal were instrumented up to a size 45 K-type file, divided into three groups of 10 teeth each and obturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
0
15
1
1
Order By: Relevance
“…In the present study, the mean time required to remove the Thermafil plastic carriers was less than the half mean time reported in the study of Frajlich et al . (1998).…”
Section: Discussioncontrasting
confidence: 72%
“…In the present study, the mean time required to remove the Thermafil plastic carriers was less than the half mean time reported in the study of Frajlich et al . (1998).…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, no significant differences of remaining filling material were observed after removal of Thermafil and laterally compacted gutta‐percha (Frajlich et al . ). A two‐dimensional evaluation of split specimens also demonstrated similar amounts of filling remnants after retreatment of Thermafil, GuttaCore and thermoplasticized gutta‐percha (Nevares et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, in retreatment cases, carrier‐based systems may be more time‐consuming or more difficult to remove completely (Frajlich et al . , Baratto et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Frajlich et al. showed that the time required for the removal of gutta‐percha with the warm vertical condensation technique was greater than with the lateral condensation technique. Thus, the number of cracks on root canal wall could be different after the retreatment of different root canal filling techniques.…”
mentioning
confidence: 99%